ANTIBACTERIAL ACTIVITY OF BEET EXTRACT ( BETA VULGARIS L. ) AGAINST GRAM-POSITIVE BACTERIA: SYSTEMATIC LITERATURE REVIEW - Sagita Ananda; Reynatha Pangsibidang; Dita Wahyuningtias (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Increasing antibiotic resistance in Gram-positive bacteria is driving the development of alternative antibacterial agents based on natural ingredients. Beetroot ( Beta vulgaris L. ) is known to contain betalain and phenol that have antibacterial potential. This study aims to analyze the antibacterial activity of Beet extract against Gram-positive bacteria and evaluate the effect of concentrations, solvents, and testing methods based on the literature during the period 2016–2026. Systematic Literature Review was conducted using the PRISMA protocol through literature searches on Publish or Perish, Google Scholar, ScienceDirect, and DOAJ databases. A total of 20 articles that met the inclusion criteria were analyzed based on the value of the inhibition zone diameter (ZI) and the Minimum Inhibitory Concentration (MIC). Beet extract showed antibacterial activity against various Gram-positive bacteria, one of which was Staphylococcus aureus with an inhibition zone range of <5–25 mm and a MIC of 0.012–32 mg/mL. Ethanol is the most widely used solvent, while the agar well diffusion method tends to produce a larger inhibition zone than disc diffusion. Beet tuber extract has the potential to be developed as a natural antibacterial source against various Gram-positive bacteria.